MODAL DAN STRATEGI MAKSIM GORKY DALAM KONTESTASI DI ARENA SASTRA DAN ARENA SOSIAL - Yunus, Muhammad Musthofa (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
Until the end of the 19th century, Russian literature was still thronged by aristocratic writers such as Tolstoy, Turgenev, and Dostoevsky. in 1880, as Tsar broaden the trade, middle classes then emerged along with new names of writers from the non-aristocratic class. Maxim Gorky is one of the writers that got recognized at that time, a writer who was born from a family of the laborer. This research aims to analyze Gorky’s initial capital and his strategy to utilize, process, and develop his capitals to be contested in the literature and social field by using Pierre Bourdieu’s concept of The Field of Cultural Production. The result of this research attests that Gorky utilizes cultural and social capital to plunge into the literature field. Gorky has possessed additional capital in the form of a specific legitimation from Chekov and Tolstoy. Gorky’s use of the capital reconvention strategy by donating money for the revolutionary movement has earned him a central role in the Russian Revolution with Lenin. other than that, social capital in the form of a close relationship with Lenin and the intellectual group was used by Gorky to face the dominant structure that has been trying to maintain the status quo and dampen the growth of Gorky’s legitimation. Gorky has also done a reproduction strategy by consistently writing revolutionary group fights and worker class-themed works. Gorky’s negotiation with Stalin in the Soviet union’s writers union is Gorky’s successive strategy to succeed the socialism realism sect he developed.